Larval morphology of Belgica antarctica Jacobs, 1900 (Diptera, Chironomidae, Orthocladiinae) from central part of the maritime Antarctic and deformities found in the larvae - Ihtimanska, Mila K.; Kovalenko, Pavlo A.; Michailova, Paraskeva V.; Parnikoza, Ivan Yu. (Zootaxa, 2023)
The larval morphology of the endemic species Belgica antarctica Jacobs, collected in January and February (2022) from six sites of Antarctica, was studied. The mouth apparatus and the parapods of one hundred seventy-six larvae were analyzed. No differences were found in the morphology of these structures between individuals of different sites. However, differences (with the exception of the length of 2nd antennal segment) were estimated in the sizes of the morphological features, as 2023 measurements were made of fifteen kinds of these structures and larval body. Deformities of mentum, mandible, antennal blade and antennal segments in percentage were established in larvae of almost all of the studied sites. The reasons for the differences and deformities are discussed.